Knowledge Sharing Mempengaruhi Innovative Work Behavior Karyawan pada Usaha Kecil dan Menengah (UKM): Peran Organizational Climate sebagai Moderator - Devi Rahnjen; Adrie Oktavio; Aria Ganna Henryanto; Andini Dwi Kurniawati; Felicia Adeline (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract: Small and Medium Entreprise (SME) is dominant business sector in Indonesia. The emergency of innovativeness among SME is necessary for surviving and sustaining competitive advantage in digitalization era and pandemic Covid – 19. Knowledge is valuable resourcess to create organizational innovation and knowledge structure can be enhanced through knowledge sharing behavior. Unfortunately, knowledge sharing may not enhance innovation in several organization. Thus, this study purpose is to examine the relationship between knowledge sharing and innovative work behavior with organizational climate as moderator. This study used partial least square analysis with 97 responden from 45 SME in Indonesia. The findings reveal that knowlegde sharing behavior affect innovative work behavior. in SME with innovativeness, afiliatation and supportve climate, knowlegde sharing behavior effect on innovative work behavior is higher. This study provide evidence that konwledge sharing behavior should be considered to improve organizational innovation. furthermore, SME’ Owner should promote innovativeness and supportive climate to enhance knowledge sharing effect on innovative behavior. Keywords: knowledge sharing behavior, innovative work behavior, organizational climate, small and medium entreprise